2014
DOI: 10.7482/0003-9438-57-013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different chromatin staining techniques for bull sperm

Abstract: Morphological analysis of semen is a very important step in fertility assessment, but many semen defects are not detectable at the morphological level. These include pathological changes in sperm chromatin structure. During mammalian spermiogenesis, histone proteins associated with DNA structure are replaced by specific protamines, with which chromatin does not form nucleosomal complexes. In the fully developed, mature sperm, the histones are replaced with protamines. Disruptions of nucleoprotein structure can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…Research conducted on young (1.5-year-old) bulls, from which sperm was isolated post mortem from the tail of the epididymis, also showed a slight deviation in the number of sperm cells with abnormally packaged genetic material (2). The present study shows that the quality of boar semen improves as sexual development progresses.…”
Section: Discussionsupporting
confidence: 58%
“…Research conducted on young (1.5-year-old) bulls, from which sperm was isolated post mortem from the tail of the epididymis, also showed a slight deviation in the number of sperm cells with abnormally packaged genetic material (2). The present study shows that the quality of boar semen improves as sexual development progresses.…”
Section: Discussionsupporting
confidence: 58%
“…Staining with silver nitrate also shows the heterogeneous structure of the sperm tail, which is probably linked to variation in the activity of mitochondria or mitochondrial derivatives. The use of silver nitrate staining to identify the sperm midpiece in other species has been described by Andraszek et al (13,14). A study by Collins and Donoghue (6) confirmed that it is useful to stain drone sperm cells using various techniques, because each technique can reveal different details of the sperm ultrastructure or defects in its morphological structure.…”
Section: Discussionmentioning
confidence: 91%
“…[21][22][23][24][46][47][48] Sperm chromatin condensation can be evaluated rapidly with aniline blue (AB). This cytochemical dye selectively stains persisting lysine-rich histones 49,50 and has been widely used to identify an excessive histone retention in the chromatin of mature spermatozoa, which has been related to infertility, poor fertilization rates and morphological defects in the sperm head. 10,14,51 However, a lower sperm chromatin condensation detected with AB does not always involve an abnormal histone content.…”
Section: Discussionmentioning
confidence: 99%